Magnetic source imaging of tactile input shows task-independent attention effects in SII - Hoechstetter, Karsten; Rupp, André; Meinck, Hans-Michael; Weckesser, Dieter; Bornfleth, Harald; Stippich, Christoph; Berg, Patrick; Scherg, Michael (Neuroreport, 2000)
We investigated whether attention to different stimulus attributes (location, intensity) has different effects on the activity of the secondary (SII) somatosensory cortex. Tactile stimuli were applied to the left index finger and somatosensory evoked fields (SEFs) were recorded using a whole-head magnetoencephalography (MEG) system. Two oddball paradigms with stimuli varying in location or intensity were performed in an ignore and an attend condition. Brain sources were estimated by magnetic source imaging. No attention effect was observed for the primary SI area. However, attention enhanced SII activity bilaterally from 55 to 130 ms by 52% in the spatial and 64% in the intensity discrimination task. SII attentional enhancement was very similar in both paradigms and occurred both for deviants and standards.
Gesehen am 04.03.2021